Ulvan from Ulva lactuca as A Potential Marine-derived Prebiotic for Functional Foods: A Review - Cepi Permana; Muhamad Rifai; Alberta Rika Pratiwi; Dyah Wulandari (Soegijapranata Catholic University, 2026)
Ulvan, which comes from the green seaweed Ulva lactuca as a sulfated polysaccharide, has gained more research interest as a possible marine-based prebiotic. The review aims to evaluate the potential of ulvan derived from Ulva lactuca as a marine-based prebiotic by analyzing studies published between 2016 and 2026. Relevant articles were collected from scientific databases focusing on ulvan characteristics, digestibility, fermentation by gut microbiota, and its potential application in functional food products. The research demonstrated through laboratory experiments and animal research that ulvan retains its original form throughout its passage from the upper gastrointestinal tract to the colon, where microbes use ulvan as their fermentation substrate. Experimental results show that the Lactobacillus and Bifidobacterium bacteria groups demonstrate higher growth rates. Fermentation products like short-chain fatty acids help maintain intestinal balance. Most available evidence comes from experimental and animal studies. The scientific community has not established whether humans show similar reactions because of a lack of thorough clinical research. Research studies show that ulvan has potential to function as a prebiotic, but it has not yet become an established prebiotic component for clinical use. Therefore, ulvan derived from Ulva lactuca represents a promising marine-based prebiotic candidate with potential application as a functional food component, although further clinical studies are required